2015
DOI: 10.1136/bmjopen-2015-007716
|View full text |Cite
|
Sign up to set email alerts
|

‘Do Well B.’: Design Of WELL Being monitoring systems. A study protocol for the application in autism

Abstract: IntroductionIndividuals with autism spectrum disorder (ASD) have difficulties in communication and social interaction resulting from atypical perceptual and cognitive information processing, leading to an accumulation of anxiety. Extreme overloading experienced internally may not be externally visible. Identifying stressful situations at an early stage may avoid socially problematic behaviour from occurring, such as self-injurious behaviour. Activation of the autonomous nervous system (ANS) is involved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The Socio-demographic characteristics questionnaire assessed age, gender, weight, size, occupational group, education level, family situation, work characteristics, physical activity, and quantity of sleep. Sleep quality, well-being and perceived stress at work and at home are evaluated using visual analogue scales (VAS), i.e., by moving a cursor on a horizontal, non-calibrated line of 10 cm, ranging from very low (0) on the left to very high (10) on the right [ 44 , 45 , 46 , 47 , 48 , 49 ]. We also looked for the presence of other addictions such as tobacco, cannabis, and alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…The Socio-demographic characteristics questionnaire assessed age, gender, weight, size, occupational group, education level, family situation, work characteristics, physical activity, and quantity of sleep. Sleep quality, well-being and perceived stress at work and at home are evaluated using visual analogue scales (VAS), i.e., by moving a cursor on a horizontal, non-calibrated line of 10 cm, ranging from very low (0) on the left to very high (10) on the right [ 44 , 45 , 46 , 47 , 48 , 49 ]. We also looked for the presence of other addictions such as tobacco, cannabis, and alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, low HRV is a marker of cardiovascular risk [ 18 ]. Conveniently, the measurement of HRV is non–intrusive and pain–free [ 19 ]. Although the evaluation of HRV in T2DM has been assessed in several studies, conflicting results have been reported [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with autism often report high levels of anxiety, 72 and many sources describe strategies aimed at reducing anxiety around data collection. Suggestions include allowing time for participants to settle in at the research site, 73 not enforcing a time limit on completing research tasks, 74 choosing “weakly stressful” stimuli for studies requiring minor stressor conditions, 75 and using visual timers, 76 as people with autism may also have timing and pacing needs 77 …”
Section: Conducting the Researchmentioning
confidence: 99%